Jumbo Bacteriophages Are Represented Within an Increasing Diversity of Environmental Viruses Infecting the Emerging Phytopathogen, Dickeya solani - Day, Andrew; Ahn, Jiyoon; Salmond, George P. C. (Frontiers in Microbiology, 2018)
Dickeya species are economically important phytopathogens widespread in mainland Europe that can reduce crop yields by 25%. There are no effective environmentally-acceptable chemical systems available for diseases caused by Dickeya. Bacteriophages have been suggested for use in biocontrol of these pathogens in the field, and limited field trials have been conducted. To date the majority of bacteriophages capable of infecting Dickeya solani, one of the more aggressive species, are from the same family, the Ackermannviridae, many representatives of which have been shown to be unsuitable for use in the field due to their capacity for generalised transduction. Members of this family are also only capable of forming individual plaques on Dickeya solani. Here we describe novel bacteriophages from environmental sources isolated on Dickeya solani, including members of two other viral families; Myoviridae and Podoviridae, most of which are capable of forming plaques on multiple Dickeya species. Full genomic sequencing revealed that the Myoviridae family members form two novel clusters of jumbo bacteriophages with genomes over 250 kbp, with one cluster containing phages of another phytopathogen Erwinia amylovora. Transduction experiments showed that the majority of the new environmental bacteriophages are also capable of facilitating efficient horizontal gene transfer, however the single Podoviridae family member is not. This particular phage therefore has potential for use as a biocontrol agent against multiple species of Dickeya.